Vistas in astronomy. - Beer, Arthur, 1900- (Journal of atmospheric and terrestrial physics. Special supplement ;, 1955)
Vol. 9 is a record of the first joint symposium of the International Astronomical Union and the Union internationale d'histoire et de philosophie des sciences, held at the University of Hamburg, Aug. 22-24, 1964.